Penelitian Keefektivitasan Pembelajaran Kanji Bahasa Jepang menggunakan Mobile Phone Berbasis Android dan Ios - Pratama, Adithya; Yordania, Yordania; Harisin, Rico; Halim, Adriani (ComTech: Computer, Mathematics and Engineering Applications, 2013)
The purpose of this research is to explore the effectiveness in learning Japanese Kanji by mobile phone, compared with learning by books. The research is conducted on two groups given same learning materials on different instructional media. The research methodology is literature study, data analysis, system design, and implementation. The test result shos that there is no significant difference in learning performance between the group using mobile phone and the group using book.